ChemInform Abstract: Homogeneous Cobalt/Vanadium Complexes as Precursors for Functionalized Mixed Oxides in Visible‐Light‐Driven Water Oxidation. Issue 52 (6th December 2016) - Pavliuk, Mariia V.; Mijangos, Edgar; Makhankova, Valeriya G.; Kokozay, Vladimir N.; Pullen, Sonja; Liu, Jia; Zhu, Jiefang; Styring, Stenbjoern; Thapper, Anders
Abstract: (NH4 )2 [Co(H2 O)6 ]2 [V10 O28 ]·4H2 O (I) and (NH4 )2 [Co(H2 O)5 (β‐HAla)]2 [V10 O28 ]·4H2 O (II) are used for the preparation of mixed oxides as catalysts for water oxidation.